Linguistic Politeness Analysis of TikTok Comments on @Kompascom’s Political News Content - Ngasrotun Ngasrotun; Sophia Rahmawati; Fania Fitri Azkaria; Gina Azzahrah; Ade Bayu Saputra (LP3M KH Yazid Karimullah Institute, 2026)
This study aims to describe the forms of linguistic politeness found in TikTok comments on the @kompascom account related to political news content based on Leech’s (1983) politeness principles. This topic is important to examine because TikTok has developed into a major digital public space in Indonesia with a very high level of interaction, particularly regarding political content. The freedom to comment in digital spaces often gives rise to various forms of speech, ranging from polite expressions to provocative statements. Therefore, this study investigates how TikTok users demonstrate linguistic politeness when responding to political news content on the @kompascom account. Previous studies have discussed linguistic politeness on TikTok in general; however, none have specifically examined political news content on the @kompascom account. Thus, this study fills that research gap. This research employs a qualitative descriptive method with a pragmatic approach. The data consisted of 10 comments selected purposively from the comment section of the @kompascom account during the period of March–April 2026. The data were collected through observation and documentation, then analyzed through data reduction, data presentation, and conclusion drawing, with theoretical triangulation used to ensure validity. All comments analyzed fulfilled the six politeness maxims proposed by Leech, namely the tact maxim, generosity maxim, approbation maxim, modesty maxim, agreement maxim, and sympathy maxim. The dominant pattern found was the delivery of criticism in a subtle manner and the establishment of agreement before expressing disagreement. The findings indicate that linguistic politeness norms are still practiced by TikTok users in the context of digital political discussions, demonstrating that communication ethics within Indonesian digital spaces have not entirely diminished and may serve as an empirical foundation for the development of digital literacy on social media platforms